Effect of white Proroot® MTA and two Thai white portland cements mixed with bismuth oxide on cementoblastic differentiation in human cementoblast-like cell line - Treesukhon Eakbannasingh (Chulalongkorn University, 2013)
Thesis (M.Sc.)--Chulalongkorn University, 2011